Autonomous Multirrotor Design and Simulation for Search and Rescue Missions - Jamett-Dominguez, M (Institute of Electrical and Electronics Engineers Inc., 2018)
In this work an autonomous multirrotor system applied to search and rescue missions is designed and simulated. This is achieved using RotorS platform, which allows to design a modular multirrotor system. The simulated multirrotor system is based in a quadrotor, an inertial measurement unit, an autopilot system, and a downward looking camera. Through the images captured by the camera, a visual odometry algorithm is simulated, obtaining multirrotor position and orientation without relying on an external location system or GPS. This gives the posibility to simulate search and rescue missions in several emergency situations modeled in RotorS as well as a testing platform for autonomous algorithms applied to multirrotors, either in search and rescue missions or other future applications, without having to expose a real system to possible damages or failures. In addition, because it is a modular design simulation environment, the multirrotor system can be modified to add new functions allowing it to be applied in various situations where autonomous control is required. © 2018 IEEE.